Thermal properties of normal and sickled hemoglobin protein - Powrel, Jhulan; Adhikari, Narayan P (BIBECHANA, 2021)
Thermodynamic properties of sickled and normal hemoglobin protein are considered within the framework of classical molecular dynamics. Here we have studied the specific heat capacity and RMSD (Root Mean Square Deviation) of both types of hemoglobin protein. Our investigation reveals that the specific heat capacity and RMSD for oxygenated hemoglobin protein is higher than those of de-oxygenated sickle hemoglobin protein. It is also observed that the specific heat capacity and RMSD values of sickle hemoglobin protein decrease with a rise in temperature.BIBECHANA 18 (1) (2021) 140-148